A quantitative method for measuring regional economic resilience to the great recession. (14th September 2018) - Ringwood, Lauryn; Watson, Philip; Lewin, Paul
Abstract: Regional economic resilience can be defined as an economy's ability to withstand and recover quickly from shocks. The ability to measure resilience is necessary to developing our understanding of what influences resilience. In this paper, we develop a new, two‐dimensional quantitative measure of resilience using observed differences between expected and actual employment in a region following a shock and distinguish the response to the shock from random variation. We demonstrate one application of this metric to US county‐level employment data to compare county responses to the 2007–2009 national recession and discuss how different regions of the United States responded to the shock of the Great Recession in terms of resilience.